Study on HIV/AIDS knowledge, sexual attitudes, sexual behaviors, and preventive services among young students in Chongqing, China - Qing, Liyuan; Wang, Yunna; Yang, Tong; Chen, Xinrui; Zhang, Meng; Bu, Qingqing; Tan, Bo; Deng, Dan (Frontiers in Public Health, 2022)
Objectives: This study aimed to describe the HIV/AIDS knowledge, sexual attitudes, and sexual behavior of young students in Chongqing, China, and to examine their use of preventive services and related factors. Method: A cross-sectional study was conducted with students from 67 schools from December 2019 to June 2021. The chi-square test or nonparametric test and logistic regression were used to analyze the factors. Confidence intervals without crossover or < 0.05 was considered significant. Results: A total of 31,782 study participants were included in the study. A total of 62.62% of the respondents were considered to be aware of basic HIV/AIDS knowledge, including 78.44%, 62.15% and 52.08% in undergraduate colleges, junior colleges and secondary vocational schools, respectively. In total, 60.96% of males and 29.42% of females were accepting of premarital sex, 15.49% of males and 6.18% of females reported being sexually experienced, and only 57.18% of the students used condoms every time they had sex. The rate of condom use among students who were aware of HIV/AIDS knowledge was higher than that among students who were not aware. A total of 85.60% of the students thought they needed HIV/AIDS prevention and control knowledge, and 94.60% thought more health education activities on HIV/AIDS prevention needed to be conducted in schools. Entrance education, lectures or consultation hotlines, WeChat official accounts and other media platforms were rated as the most acceptable HIV/AIDS prevention education methods. Conclusion: An increasing number of students show an open attitude towards premarital sex and engage in risky sexual behavior. It is urgent to enhance and widely disseminate comprehensive HIV/AIDS and sexual health education in multiple formats.